Winning a battle against the odds: A cleaners' campaign. (February 2023) - Pannini, Elisa
This article analyses a campaign urging a British university to re-establish in-house cleaning services after years of outsourcing. The small independent union leading the campaign began from an extremely low level of power resources and managed to build enough associational and societal power to win the dispute on cleaners' working conditions. The study is based on participant observation of the union's activities, document analysis and interviews. The article argues that the strategy emerging from the study, centred around three key strategies (collectivization of individual grievances, education, and disruption of core business activities), can be articulated in a process following the main categories of Mobilization Theory: organization, mobilization and collective action. Additionally, the union managed to conciliate servicing and organizing strategies, as well as attention to class-oriented and migrant-specific issues.